TEACHING PART OF SPEECH AND WORD GROUPS AS UNITS OF MEANING IN ESP SPEAKING CLASS - Rahmah, Urwatus Silvia (Journal of English for Academic and Specific Purposes (JEASP), 2018)
English for Specific Purposes (ESP) is known as a learner-centeredapproach to teach English as a foreign or second language. Students learnEnglish for a specific purpose, represented by studying subject matter, togain and develop appropriate knowledge and skills through English. Theyhave to perform task in English, meanwhile they are also supposed to bemastered in speaking skill. The objective of this paper is to build thestudent’s speaking ability effectively by using English. Teaching part ofspeech and word groups as units of meaning are used in the class. Theyhave to know the words first and then able to classify them as basic oftheir speaking. The activities include in some parts, they have listeningsection to start the activity, then grouping the students and asking themto tell the information in front of the class. The aims of this activity are toencourage their competence in English speaking and also make theminvolve in speaking class. Thus, this paper aims to give a clear explanationand a deeper insight about teaching part of speech and word groups asunit of meaning, stimulate all of teachers of ESP to implement thematerial in their teaching processes and make them realize in choosing theappropriate material to teach their students.